Competition and facilitation between Australian and Spanish legumes in seven Australian soils - Pérez-Fernández, M.; Lamont, Byron (2015)
This paper evaluates the relative performance and competitive ability of seven legumes from the Iberian Peninsula, Spain (one already invasive in Australia), grown singly or pairwise with seven legumes from south-western Australia in their own soils. Indices of growth used were root, shoot and total mass and shoot dimensions. Water content, xylem water potential during drying and nodule production were also measured. The index of competition used was the intensity of competition coefficient (ICC), which is suitable for additive designs. The Australian species usually grew larger than the Spanish species, in their presence or absence, although the results were sensitive to the index of growth or resource capture used. The Australian legumes usually possessed greater total water content than the co-occurring Spanish legumes. At least five Australian species were less reduced or not affected at all by inter-regional competition compared with growth in isolation. Two Australian legumes performed relatively poorly in the presence of at least four Spanish legumes. The ICC identified many instances of growth promotion (facilitation) of the Australian species, which we attribute to extra nitrogen obtained through enhanced nodulation of both cohabiting species. Five of the seven Spanish species were outcompeted by the Australian species, whereas the growth of two was sometimes facilitated. Although the Spanish legumes had greater competitive ability in the more fertile Australian soils, they remained competitively inferior to the Australian legumes in their first season of growth and none is likely to displace the native legumes at this stage of growth. Longer-term field studies are needed to fully evaluate the potential invasiveness of perennial legumes.